Notch Signaling Inhibition by LY411575 Attenuates Osteoblast Differentiation and Decreased Ectopic Bone Formation Capacity of Human Skeletal (Mesenchymal) Stem Cells. (22nd August 2019) - AlMuraikhi, Nihal; Ali, Dalia; Vishnubalaji, Radhakrishnan; Manikandan, Muthurangan; Atteya, Muhammad; Siyal, Abdulaziz; Alfayez, Musaad; Aldahmash, Abdullah; Kassem, Moustapha; Alajez, Nehad M.
Abstract : Background . Chemical biology approaches using small molecule inhibitors targeting specific signaling pathways are useful tools to dissect the molecular mechanisms governing stem cell differentiation and for their possible use in therapeutic interventions. Methods . Stem cell signaling small molecule library functional screen was performed employing human bone marrow skeletal (mesenchymal) stem cells (hBMSCs). Alkaline phosphatase (ALP) activity and formation of mineralized matrix visualized by Alizarin red staining were employed as markers for osteoblastic differentiation. Global gene expression profiling was conducted using the Agilent microarray platform, and data normalization and bioinformatics were performed using GeneSpring software. Pathway analyses were conducted using the Ingenuity Pathway Analysis (IPA) tool. In vivo ectopic bone formation was performed using hBMSC mixed with hydroxyapatite–tricalcium phosphate granules that were implanted subcutaneously in 8-week-old female nude mice. Hematoxylin and eosin staining and Sirius red staining were performed to identify bone formation in vivo . Results . Among the tested molecules, LY411575, a potent γ -secretase and Notch signaling inhibitor, exhibited significant inhibitory effects on osteoblastic differentiation of hBMSCs manifested by reduced ALP activity, mineralized matrix formation, and decreased osteoblast-specific gene expression as well as in vivo ectopic bone formation. Global gene expression profiling of LY411575-treated cells revealed changes in multiple signaling pathways, including focal adhesion, insulin, TGF β, IL6, and Notch signaling, and decreased the expression of genes associated with functional categories of tissue development. Among the affected signaling networks were TGF β 1, SPP1, and ERK regulatory networks. Conclusions . We identified γ -secretase inhibitor (LY411575) as a potent regulator of osteoblastic differentiation of hBMSC that may be useful as a therapeutic option for treating conditions associated with ectopic bone formation.